Pengaruh Fasilitas Pendukung Fisik dan Kualitas Pelayanan terhadap Kepuasan Tamu Menginap di Ocean Beach Hotel Padang - Raisya Rasheka Ramadhanti; Youmil Abrian (Jurnal Manajemen Pariwisata dan Perhotelan, 2023)
This research is motivated by a phenomenon related to guest satisfaction stayed at Ocean Beach Hotel Padang, where the were several complaints regarding the physical evidence and quality of service. This research purpose to reveal the physical evidence and quality of service effect on the satisfaction from guest staying at Ocean Beach Hotel Padang. This research type is associative research using quantitative data. The method used in this research is a survey method by distributing questionnaires. The research population were guests who had stayed at least once with a sample of 240 respondents. The technique for sampling is non probability sampling through purposive sampling technique. Collecting data in this study using a questionnaire with five answer choices. This study was adapted from previous research and has been tested for validity and reliability. Data analysis used linear regression analysis. The research results indicate that physical evidence (X1) effect om guest satisfaction (Y) and quality of service (X2) has an effect on satisfaction from guest (Y). This can be seen with a small sig value of 0.05.